Recognition of healthy and cancerous breast cells: Sensing the differences by dielectric spectroscopy. Issue 10 (28th August 2020) - Ambrico, M.; Lasalvia, M.; Ligonzo, T.; Ambrico, P. F.; Perna, G.; Capozzi, V.
Abstract : Purpose: The response of human cells to applied electrical signals depends on the cellular health status, because it is influenced by the composition and structure of the main cellular components. Therefore, electrical impedance‐based techniques can be considered as sensitive tools to investigate healthy or disease state at cellular level. The goal of this study is to show that different types of in vitro cellular lines, related to different health status, can be differentiated using impedance spectra analysis. Methods: Three different types of human breast cell line, corresponding to healthy, cancerous, and metastatic adenocarcinoma cells, were measured by means of electrical impedance spectroscopy. By modeling the investigated cells with proper resistive and capacitive circuital elements, the magnitude of the cell electrical components and spectra of real and imaginary part of dielectric permittivity were obtained. The latter were subsequently examined with a commonly adopted mathematical model, in order to estimate the values of specific dielectric parameters for the three different cellular lines. Results: The relative variation of cellular capacitance with respect to that of the culture medium, estimated at 100 Hz, has a larger value for the two types of cancerous cells with respect to the noncancerous type. Furthermore, the ratio between the real and imaginary part of the dielectric permittivity function has larger values for metastatic cells with respect to the normal and nonmetastatic ones. Therefore, the mentioned relative capacitance allows to discriminate between normal and cancerous cells, whereas the results obtained for the dielectric function can discriminate between metastatic and nonmetastatic cells. Conclusions: This study can be considered as an exploratory investigation of evaluating in vitro the health status of humans cells using selected electrical impedance parameters as potential markers. The obtained results highlight that a standard cultureware system, provided with interdigitated electrodes and appropriate impedance parameters, that is, cellular capacitance and the ratio between the imaginary and real part of cellular dielectric function, can be used to discriminate between healthy and cancerous breast cell lines, as well as different malignancy degrees.